DESAIN PEMASARAN DIGITAL, KEMASAN DAN LABEL PADA UMKM EMBAL IBU BAINA NEGERI YAPUTIH KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - M. Faqih Fauzan Tehuayo; Dian Utami Sutiksno; Evandro A. W. Manuputty (Jurnal Administrasi Terapan, 2022)
Ibu Baina's embalming business does not have digital media marketing Facebook, Instagram, and is not even recorded on Google Maps. Packaging only uses ordinary plastic bags for products. the packaging used is not safe food grade for packing food/beverage products, does not have a packaging product label. the goal to be achieved is to carry out a marketing strategy "designing digital marketing, packaging and labels for MSMEs Embal Ibu Baina.This research is applied research that aims to provide solutions to certain problems and this applied research is included in the type of action research. The object of this research is Baina Negeri Yaputih's embal business. The analysis technique used in this study refers to the Miles and Huberman model or interactive data analysis, namely: data collection, data reduction, data presentation, and verification/drawing conclusions.The author makes digital marketing alternatives starting from registering business locations on Google Maps, creating Facebook accounts and Instagram accounts. In addition, there are design stages to innovating plastic bag packaging into standing pouch packaging with a thickness of 120 microns, procuring product labels using the Canva application as a design medium and Waterproof Glossy Photo Paper sticker with a label size of 10 x 14 cm as label material. Business places that are not recorded on Google Maps are registered so that potential customers can easily find a place of business, create Facebook and Instagram accounts that aim to sell and market products. using a 20 x 29 cm standing pouch to innovate packaging from old packaging/plastic bags and design labels that are not owned by the standard IRT (Household Industry) label Keywords: Marketing, Packaging, Labels, Products.